Bioinspired soft caterpillar robot with ultra-stretchable bionic sensors based on functional liquid metal. (June 2021) - Jin, Guoqing; Sun, Yuyang; Geng, Jiangjun; Yuan, Xin; Chen, Tao; Liu, Huicong; Wang, Fengxia; Sun, Lining
Abstract: Soft robots have significant advantages in terms of flexibility and adaptability, leading to potential applications in the bionics field. Inspired by the caterpillars in nature, this work proposed a soft caterpillar robot (SCR) by integrating two types of ultra-stretchable bionic sensors on a dual air-chamber pneumatic network structure. In order to realize self-powered tactile sensing, four triboelectric nanogenerator tactile sensors (TTSs) based on functional liquid metal (FLM) with thorny-structured bionic whiskers are developed and attached on the SCR. Meanwhile, two ultra-stretchable resistive strain sensors (RSSs) by using FLM are covered as the bionic skin to sense self-body deformation of the SCR. The TTS has a fast response time of 0.03 s and a minimum perception of 0.05 kPa, which can be very sensitive to the unknown stimulus of various materials. The RSS with a relatively high sensitivity of 2.94 and small hysteresis of 1.42% possess the ultra-stretchable ability of 180% strain, which helps to adapt and adjust its own body bending and crawling. The biological perception capabilities of the SCR play a crucial role in mimicking bionic actions and response in an unknown environment, such as escaping from unexpected attacks as well as adaptive crawling through an unknown tunnel environment. Graphical Abstract: Soft robots have significant advantages in terms of flexibility and adaptability, leading to potential applications in the bionics field. Inspired by the caterpillars in nature, this work proposed a soft caterpillar robot (SCR) by integrating two types of ultra-stretchable bionic sensors on a dual air-chambers of pneumatic network structure. In order to sense self-body deformation of the SCR, two ultra-stretchable resistive strain sensors (RSSs) by using functional liquid metal (FLM) are covered as the bionic skin. Meanwhile, four triboelectric tactile sensors (TTSs) based on FLM with thorny-structured bionic whiskers are developed and attached on the head, tail and body of the soft caterpillar, respectively, to realize self-powered tactile sensing. The biological perception capabilities of the SCR play a crucial role to mimic bionic actions and response in an unknown environment, such as escaping from unexpected attacks as well as adaptive crawling through an unknown tunnel environment. ga1 Highlights: The ultra-stretchable bionic sensors based on FLM were integrated on a SCR to realize bionic sensing. The TTS was sensitive to the unknown stimulus of various materials. The RSS was sensitive to the bending of SCR. Closed-loop control enabled SCR to achieve intelligent sensing and automatic motion.